(untitled) (Indian Journal of Child Health, 2024)
Autism spectrum disorder (ASD) is a complex formative condition, described by tenacious difficulties in social cooperation and correspondence and confined and dreary behavior. There is no solution for Autism and a few treatments are accessible as well as certain drugs to further develop life for impacted youngsters and grown-ups. This paper presents a case of a boy who was treated from the age of 8 years with Yoga Prana Vidya (YPV) healing complementarily to other therapies achieving positive progress. This study uses the case study method by going through the patient’s medical records, the healer’s records, and the patient’s mother’s feedback. YPV healing was applied as a long-term intervention spanning 3 years, complementary to home-based “Son-Rise” program therapy. Within the first 15 days of YPV healing, the boy’s improvements were noticeable, and progress began after a stagnant condition over the previous 2 years. After 3 months of YPV intervention, the boy became more receptive to faster learning. After a year of healing, the boy’s condition improved from Grade 1 to Grade 2 of the “Son-Rise” gradation. At the end of the 3rd year, the boy achieved most of the Grade 3. YPV healing is being continued further. The integrated and holistic system of YPV healing therapy was successfully applied to the autism case as a complementary therapy, achieving the patient’s faster progress, and enabling parents to overcome social stigma. Further research is recommended on the application of YPV healing therapy in the treatment of ASD.